The intercontinental search for the other: A study of the “Epistle of Amaryllis to Belardo” - Rojas Pachas , Daniel (2026)
This study examines the letters exchanged between the Spanish poet Félix Lope de Vega and the Peruvian writer Amarilis. Both texts are published in the 1621 book La Filomena. The research involves a discursive analysis of two texts that reveal an intercontinental dialogue, cultural syncretism, and the need to be engaged by another who lives on the other side of the world. Based on the theoretical postulates of Mikhail Bakhtin, Hans-Georg Gadamer, and Dominique Maingueneau, the study examines the perspective that operates on otherness, the exotopic movement that involves the reconstruction of the self, and communication as a form of encounter grounded in playfulness and authorial ethos. The study addresses these Ibero-American authors’ need to construct an imaginary that transcends utopia and to give concrete form to the imagined place beyond their own borders, to the point of being challenged by a voice from distant latitudes.